Combining adult stem cells and olfactory ensheathing cells: the secretome effect - Silva, N. A. (2013)
Adipose-derived adult stem cells (ASCs), bone marrow mesenchymal stem cells (bmMSCs), and human umbilical cord perivascular cells (HUCPVCs) tissue have been widely tested for regenerative applications, such as bone regeneration. Moreover, olfactory ensheathing cells (OECs) show promise in promoting spinal cord injury (SCI) regeneration. Our group recently proposed the use of a hybrid scaffold targeting both vertebral bone repair and SCI regeneration. According to this concept, both MSCs and OECs should be in close contact to be influenced by the factors that are involved in secretion. For this reason, here we studied the effects of the OEC secretome on the metabolic activity and proliferation of ASCs, bmMSCs, and HUCPVCs. The stem cells’ secretome effects on metabolic activity and proliferation of the OECs were also considered. In co-cultures of OECs with ASCs, bmMSCs, or HUCPVCs, the metabolic activity/viability, proliferation, and total cell numbers were measured after 2 and 7 days of culture. The results demonstrated that the secretome of OECs has a positive effect on the metabolic activity and proliferation of MSCs from different origins, especially on ASCs. Furthermore, in general, the stem cells’ secretome also had a positive effect on the OECs behavior, particularly when ASCs were in co-culture with OECs. These results suggest that the most suitable combination of cells to be used in our hybrid scaffold is the OECs with the ASCs. Finally, this work adds new knowledge to the cell therapy field, bringing new information about paracrine interactions between OECs and distinct mesenchymal stems